1955
DOI: 10.1083/jcb.1.6.551
|View full text |Cite
|
Sign up to set email alerts
|

The Fine Structure of the Renal Glomerulus of the Mouse

Abstract: Sections of mouse renal glomerulus fixed by perfusion with buffered osmium tetroxide solution have been studied with the electron microscope. Four components are recognized in the mouse glomerulus: epithelium, basement membrane, endothelium, and intercapillary cell. The three cellular components all display in their cytoplasm mitochondria, Golgi bodies, endoplasmic reticulum, and uncharacterized vesicles. The concepts of Hall, of Pease, and of Rhodin regarding the glomerular filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

1957
1957
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(41 citation statements)
references
References 23 publications
2
36
0
2
Order By: Relevance
“…Non-diabetic hamsters. The glomcruli of a young hamster did not differ from the glomeruli of other animals, which have been described by many investigators [47,30,14,41,28]. The epithelial cells had fine foot and one in a hamster with early-onset diabetes in the early stage (right).…”
Section: I Electron Microscopic Findingssupporting
confidence: 55%
“…Non-diabetic hamsters. The glomcruli of a young hamster did not differ from the glomeruli of other animals, which have been described by many investigators [47,30,14,41,28]. The epithelial cells had fine foot and one in a hamster with early-onset diabetes in the early stage (right).…”
Section: I Electron Microscopic Findingssupporting
confidence: 55%
“…2 Lipid rafts are plasma membrane microdomains that are highly enriched in cholesterol and glycosphingolipids, 3,4 and serve as platforms for many crucial intracellular signaling proteins. 2 Two different types of lipid rafts exist: the caveolae, which are highly enriched in proteins from the caveolin family, 5,6 and non-caveolar lipid rafts, which are characterized by their expression of flotillin-1 and flotillin-2, Flot2 (also known as reggie-2 and reggie-1, respectively 7 ). Flotillins were initially thought to be associated with caveolae, 8 but it was later shown that lipid rafts containing flotillin microdomains were distinct from caveolae.…”
Section: Introductionmentioning
confidence: 99%
“…It has emerged that capillaries of different tissues or of different parts of the same tissue may vary in some of their features, such as the prominence of the basement membrane or the investing layer of periendothelial cells (12). With one or two exceptions, notably the glomerular capillaries (42,156), these small vessels have essentially similar characteristics, recently summarized by Fawcett (31). The first point revealed by electron microscopy was that the hypothetical endocapillary layer either does not exist or is not preserved by current techniques, the former seeming more likely since blood cells may be seen virtually in contact with the endothelial surface.…”
Section: Ultrastructure Of the Normal Capillary And Venulementioning
confidence: 85%